2017
DOI: 10.4140/tcp.n.2017.341
|View full text |Cite
|
Sign up to set email alerts
|

Marijuana Use in the Elderly: Implications and Considerations

Abstract: With this review, pharmacists will be informed on recommendations on the use of marijuana in the older adult. Monitoring of therapy, as well as adverse effects, will be reviewed, including some legal issues and challenges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…Marijuana use has been associated with injury ( Asbridge et al, 2014 ; Blows et al, 2005 ; Choi, Marti, et al, 2017 ; Wettlaufer et al, 2017 ), mental health problems ( Choi et al, 2016 ; Choi et al, 2016a ; Hall & Degenhardt, 2009 ; Manrique-Garcia et al, 2012 ), cardiovascular disease ( Alshaarawy & Elbaz, 2016 ; Hackam, 2015 ; Hemachandra, McKetin, Cherbuin, & Anstey, 2016 ; Lindsay, Foale, Warren, & Henry, 2005 ; Reece, Norman, & Hulse, 2016 ), respiratory problems ( Howden & Naughton, 2011 ; Macleod et al, 2015 ; Martinasek, McGrogan, & Maysonet, 2016 ; Moore, Augustson, Moser, & Budney, 2005 ), metabolic syndrome ( B. A. Yankey, Rothenberg, Strasser, White, & Okosun, 2017 ; B. N. Yankey, Strasser, & Okosun, 2016 ), cancer ( Aldington et al,2008a , 2008b ; Zhang et al, 1999 ), unhealthy diet ( Foltin, Fischman, & Byrne, 1988 ; Smit & Crespo, 2001 ), and drug–drug interactions ( Lasota, 2015 ; Mahvan et al, 2017 ). In addition, the use of marijuana with other substances, including prescription drugs, tobacco, alcohol, and other illicit substances, may exacerbate the negative effects of marijuana use in aging bodies.…”
Section: Discussionmentioning
confidence: 99%
“…Marijuana use has been associated with injury ( Asbridge et al, 2014 ; Blows et al, 2005 ; Choi, Marti, et al, 2017 ; Wettlaufer et al, 2017 ), mental health problems ( Choi et al, 2016 ; Choi et al, 2016a ; Hall & Degenhardt, 2009 ; Manrique-Garcia et al, 2012 ), cardiovascular disease ( Alshaarawy & Elbaz, 2016 ; Hackam, 2015 ; Hemachandra, McKetin, Cherbuin, & Anstey, 2016 ; Lindsay, Foale, Warren, & Henry, 2005 ; Reece, Norman, & Hulse, 2016 ), respiratory problems ( Howden & Naughton, 2011 ; Macleod et al, 2015 ; Martinasek, McGrogan, & Maysonet, 2016 ; Moore, Augustson, Moser, & Budney, 2005 ), metabolic syndrome ( B. A. Yankey, Rothenberg, Strasser, White, & Okosun, 2017 ; B. N. Yankey, Strasser, & Okosun, 2016 ), cancer ( Aldington et al,2008a , 2008b ; Zhang et al, 1999 ), unhealthy diet ( Foltin, Fischman, & Byrne, 1988 ; Smit & Crespo, 2001 ), and drug–drug interactions ( Lasota, 2015 ; Mahvan et al, 2017 ). In addition, the use of marijuana with other substances, including prescription drugs, tobacco, alcohol, and other illicit substances, may exacerbate the negative effects of marijuana use in aging bodies.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the evidence supports a benefit for the use of medical cannabis for chemotherapy-induced nausea and vomiting; bladder frequency, pain, and spasticity in multiple sclerosis; and glaucoma. ( 14 ) Some small, preliminary studies have suggested a potential benefit of using cannabis for the relief of symptoms associated with PTSD. ( 15 ) CBD extract may also be of benefit in certain psychiatric conditions such as Social Anxiety Disorder and schizophrenia, ( 16 ) although the data on efficacy and safety remains very limited and may not be applicable to older adults due, in part, to age-related changes in pharmacodynamics and pharmacokinetics.…”
Section: Introductionmentioning
confidence: 99%
“…For these people, MC might offer a way of managing symptoms with fewer side effects, in a situation with a good possibility of decreasing administered drug usage [3,7,28,29] . Moreover, although some recent studies have shown increasing use of cannabis by the elderly, only a few such populations have been analyzed [23,30,31] and to the best of our knowledge, no one has analyzed the use of MC in a nursing home.…”
Section: Discussionmentioning
confidence: 99%